Synergistic effects of gadolinium oxide into the matrix of zeolitic imidazolate frameworks (ZIFs) for supercapacitor applications - Imosobomeh L. Ikhioya; Nawal Alghamdi; Stanley Ebubechukwu Omeje; David Chibiuke Ikeh; Ruth Ngozi Odoh (Chemistry of Inorganic Materials)
In this study, we synthesized ZIF-8, ZIF-67, Gd₀.₀₁/ZIF-8, & Gd₀.₀₁/ZIF-67 electrodes using the direct combination technique. Both electrodes are being used for energy storage devices. We extensively evaluated these nanocomposites using a variety of electrochemical methods, including retention analysis, galvanostatic charge-discharge (GCD), cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS). ZIF-8 exhibits a wide band gap of approximately 2.58 ​eV, suggesting its main absorption is of UV light. The peaks in the absorbance spectrum vary slightly in wavelength due to the presence of different metal centers. Peaks between 1400 and 1600 ​cm⁻1 indicate C–N stretching vibrations from the imidazolate linkers. Peaks between 1600 and 1700 ​cm⁻1 are associated with CC stretching vibrations. ZIF-8 exhibits well-defined peaks in its XRD pattern, indicating a high level of crystallinity. Peaks can be observed at specific 2θ values, typically at 22.09°, 26.62°, 38.49°, and 47.27°, which correspond to the (110), (200), (211), and (220) planes. The calculated specific capacitances for ZIF-8 and ZIF-67 are 223.95 and 255.20 ​F/g. For Gd0.01/ZIF-8, & Gd0.01/ZIF-67 specific capacitances are 575.00 and 587.50 ​F/g. The ZIF-8, ZIF-67, Gd0.01/ZIF-8, & Gd0.01/ZIF-67 electrodes exhibited specific capacitances of (78.30, 192.59, 342.57, and 1164) F/g at current densities of 1 A/g from the GCD calculation. The retention plot of ZIF-8, ZIF-67, Gd0.01/ZIF-8, & Gd0.01/ZIF-67 electrode shows efficiency of 71 ​%, 71 ​%, 105 ​% and 75 ​%, respectively, indicating their suitability for supercapacitor applications.